ECONOMIC, SOCIAL AND ENVIRONMENTAL SAFETY OF PIPE ROLLING ENTERPRISES: RELATIONSHIP, PURPOSE AND OBJECTIVES - Suglobov, A.E; Malyutina, T.D (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
At the macro level, the last ten years have provided explanations for understanding the scale of the challenges we face in the area of sustainable development, as well as for the possibilities for building a more sustainable world. If we want to fully unlock the potential for sustainable development, all members of the global economic community must come together to tackle the major challenges facing businesses, people, and our planet as a whole. Today, multinational companies are aware that a sustainable development strategy has become an urgent necessity, and that international business can influence the global sustainable development agenda to create a more inclusive economy. Faced with complex economic, social, and environmental problems against the background of General instability in the business environment, companies are increasingly seeking to win and maintain the trust of their stakeholders. Business objectives are no longer limited to making a profit, but today they are focused on the fact that companies expand their own ambitions, aiming at obtaining long-term benefits associated with the implementation of opportunities in the field of environmental and socio-economic sustainable development, which in turn contributes to the strengthening of economic security of these subjects.